“Narrative Transformations” in Texts of Non-Classical Artistic Paradigm (Cinema, Literature) - E. V. Abramovskikh (Научный диалог)
The principles and methods of violation of the narrative statements of the text are examined. Typologically similar trends in the use of “narrative transformations” in literature and cinema are shown. The fundamental difference of their implementation in various symbolic systems is commented. The paper shows that the narrative transformations in the film text are: openness of composite construction (violation of the order of the parts, skip parts, open end), fragmentation; plot polysemy (multiplicity); polysubjectness; gaps (space of uncertainty). Special attention is paid to non-narrativity as the main strategy of non-classical artistic paradigm, defined as a lack of event experience of being. This problem is related to the crisis of I-consciousness, for which the destruction of the personal event experience means the loss of self-identity. Narrative transformations are discussed in the following films: “Irreversible” (dir. Gaspar Noé), “Descended from heaven” (dir. V. Kunin), “Lock, Stock and Two Smoking Barrels” (dir. Guy Ritchie), “Rashomon” (dir. A. Kurosawa), “Trans-Europ-Express” (dir. A. Robbe-Grillet), “Reconstruction” (dir. Christoffer Boe), “Groundhog Day” (dir. X. Ramis), “Run, Lola, run” (dir. T. Tykwer), “Empty house” (dir. Kim Ki-Duk), “No trains, no planes” (dir. Jos Stelling), “Amelie” (dir. Jean-Pierre Jeunet), etc.